ISOLATION OF PROTEINS FROM SACHA INCHI (PLUKENETIA VOLUBILIS L.) IN PRESENCE OF WATER AND SALT - MF, QUINTEROS; R, VILCACUNDO; C, CARPIO; W, CARRILLO (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The aim of this study was to obtain protein isolate from sacha inchi using alkaline pH at different pHs of precipitation with water and salt and to analyze protein isolate with electrophoresis. Methods: Sacha inchi protein isolates were obtained using isoelectric precipitation method at different pHs. Proteins were analyzed using electrophoresis native-polyacrylamide gel electrophoresis (PAGE), one-dimensional, two-dimensional-sodium dodecyl sulfate-PAGE. Results: A yield of 20.88% of protein isolate of defatted sacha inchi flour at pH 4.0 with a 75.31% of protein was obtained. The yield of protein isolate using water and salt was similar. Polypeptides profile is between 14 and 70 kDa. Conclusions: Sacha inchi seed is a good source of proteins. Globulins and albumins were identified in the sacha inchi protein isolate in the presence of water and salt. Keywords: Albumins, Globulins, Proteins, Protein isolate, Sacha inchi.